1. The problem statement, all variables and given/known data Using the function of a function formula differentiate the following: y = (cos 2x)3 2. Relevant equations dy/dx = dy/du * du/dx 3. The attempt at a solution y = (cos 2x)3 u = cos 2x y = u3 dy/du = -2sin2x du/dy = 3u2 dy/dx = dy/du * du/dx dy/dx = -2sin2x * 3(cos2 2x) = -6sin2x cos22x Hi, I've been racking my brain over this question for sometime now, I've attempted it multiple times getting it wrong over and over again. I've got this answer, but, I'm really not confident that it is right. Can you guys take a look at it and work some magic? It's function of a function, which I think is more commonly known as the Chain rule. Thank you.